Photo Catalytic Degradation of Reactive Blue 4 Dye using Hydrothermal Synthesized ZnO Nanoparticles - Hassan A. Alshamsi (Journal of Global Pharma Technology, 2018)
The research reports the preparation of zinc oxide nanoparticles (ZnO NPs) using hydrothermal process. Several techniques were used to characteristic ZnO NPs which included x-ray diffraction (XRD), scanning electron microscopy (SEM) ,transmission electron microscopy (TEM),atomic force microscope (AFM),and Fourier-transform I Infrared Spectroscopy (FTIR).Also, the research included photo catalytic activity of ZnO NPs for Reactive Blue 4 dye removal from aqueous solution under light irradiation from 100 W . It was shown that the use of ZnO as photo catalyst have acceptable photo catalytic activity for degradation of dye. It has been found that maximum percentage removal of dye was achieved at 0.8g/L ZnO mass, pH 6, temperature 303K and dye concentration 20 ppm. The photo catalytic degradation was monitored by measuring the absorbance of the dye at its λ max using UV-Vis spectroscopy.Keywords: Hydrothermal, ZnO, nanoparticles, Photo catalyst, dye, SEM.